Analisis Strategi Bersaing Pasar Kaget untuk Memenangkan Persaingan - Purwanto Purwanto; Anaconda Bangkara (Jurnal Manajemen dan Bisnis Indonesia, 2016)
The problem companies are becoming increasingly complex and competitive business be increased very sharply, as a result of changes in the business environment in the era of globalization. Companies must be able to adapt to the environment in order to survive in the midst of these conditions. For that management is required to manage the organization in a better and more professional in controlling the activities of the company. Business "shock market" Cikarang, Jababeka, Bekasi as a collection of merchants who sell various products to lower middle class should immediately anticipate and prepare for making new business strategies to survive and thrive in the future. The study has the purpose of analyzing the external and internal business environment, identifying, evaluating business strategies and finding alternative strategies for the future that can be implemented " shock market.â€ External business environment will be analyzed with descriptive qualitative method involving shared business environment (economic, political, ecological and technological), Porter's competitive forces, the forces of the trigger and the key success factors.The results showed that the manager should earnestly follow external analysis results such as politics, economics and ecology as well as industrial environments (competition among members of the industry, the threat of new entrants, threat of substitute products, buyer powerful and strong supplier) Keywords : market shock, the external business environment , the strength of competition Porter